Improving literacy about the cultivation and utilization of family medicinal plants in Blunyahrejo Village, Yogyakarta City - Wahyuningsih, Mae Sri Hartati; Najiyati, Ifa; Wastutiningsih, Sri Peni; Purwono, Setyo; Padmawati, Retna Siwi (Journal of Community Empowerment for Health, 2025)
Introduction: During the COVID-19 pandemic, Indonesian society used family medicinal plants to prevent infection by enhancing immunity. Consumption of medicinal plants as herbal medicine should have scientific consideration so that the benefits can be proven and do not cause harmful side effects. Cultivation of medicinal plants is necessary to meet the needs of the family's medicinal plants independently.Methods: We designed a community-based education to improve literacy about the cultivation and utilization of family medicinal plants to farmer groups at Blunyahrejo, Yogyakarta. The study used a quasi-experimental research design with one group pre-post-test design. The group received an intervention in the form of training on the use and cultivation of medicinal plants. Community literacy was measured before and after participants attended the training. The 1st post-test has been conducted right after the training and the 2nd post-test was carried out after 3 months of intervention. The data were analyzed by a paired t-test.Results: The total number of participants who participated was 28 people. Observations have also been done during and after the training. The study showed that there was an increase in knowledge about the cultivation and utilization of family medicinal plants between the pre-test and 1st post-test, 1st post-test and 2nd post-test, and the pre-test and 2nd post-test (9.96%; 1.98%; 12.04%).Conclusion: The training improved the literacy about the cultivation and utilization of family medicinal plants of the farmer group in Blunyahrejo, Yogyakarta. Although the number of participants was quite small, participants showed a positive response during and after the training. Community leaders often reported the activities of farmer groups that showed enthusiasm for maintaining and continuing the cultivation of medicinal plants after the training.